1995
DOI: 10.1897/1552-8618(1995)14[571:lalsia]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Linear Alkylbenzenesulfonate (Las) Surfactants in a Simple Test to Detect Refractory Organic Carbon (Roc): Attribution of Recalcitrants to Impurities in Las

Abstract: The standard procedure to examine the biodegradability of a (group of) compound(s) in a trickling filter is a continuousflow system. In this test, nondegraded metabolites from a commercial linear alkylbenzenesulfonate (LAS) surfactant are detected (Kolbener, Baumann, Leisinger, and Cook; accompanying paper). This procedure has now been augmented by two phases in closed cycle to give a test for refractory organic carbon (ROC test). First, the concentration of nondegraded metabolites was increased by readdition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 7 publications
3
37
0
1
Order By: Relevance
“…1) is fully biodegradable (21,22), and degradative organisms were isolated in laboratories which did not have extensive analytical capabilities to explore their physiology in detail (13,16,33). Schulz et al (32) found that their isolate, D. acidovorans SPB1, has a very narrow substrate spectrum for SPCs, namely, RS-2-C4-SPC, which are degraded sequentially, the S enantiomer first.…”
Section: Discussionmentioning
confidence: 99%
“…1) is fully biodegradable (21,22), and degradative organisms were isolated in laboratories which did not have extensive analytical capabilities to explore their physiology in detail (13,16,33). Schulz et al (32) found that their isolate, D. acidovorans SPB1, has a very narrow substrate spectrum for SPCs, namely, RS-2-C4-SPC, which are degraded sequentially, the S enantiomer first.…”
Section: Discussionmentioning
confidence: 99%
“…The eluate from the trickling filter was chromatographed (26), the fractions corresponding to the desired material were collected and subjected to solidphase extraction to remove the perchlorate in the mobile phase (28), and the neutralized material was used in growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas the degradation of LAS is well established (16,26,27,35,39,43), the mechanisms of its degradation are not (4).…”
mentioning
confidence: 99%
“…Insufficient biodegradation led to the accumulation of big masses of foam in streams and rivers. For example, the branched-chain alkylbenzenesulfonate (ABS) surfactants, which resisted biodegradation, were replaced by linear alkylbenzenesulfonate (LAS) surfactants, which are completely biodegradable (Ghazali, 2002;Kö lbener et al, 1995). Also, biodegradable biosurfactants have been used and compared with synthetic surfactants with promising results (Makkar and Rockne, 2003) on bioremediation applications.…”
Section: Introductionmentioning
confidence: 99%